2021
DOI: 10.3389/fpls.2021.703283
|View full text |Cite
|
Sign up to set email alerts
|

Lens orientalis Contributes Quantitative Trait Loci and Candidate Genes Associated With Ascochyta Blight Resistance in Lentil

Abstract: Australian lentil production is affected by several major biotic constraints including Ascochyta blight (AB), caused by Ascochyta lentis, a devastating fungal disease. Cultivation of AB resistant cultivars, alongside agronomic management including fungicide application, is the current most economically viable control strategy. However, the breakdown of AB resistance in cultivars, such as Northfield and Nipper, suggests the need for introgression of new and diverse resistance genes. Successful introgression ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 71 publications
0
11
0
Order By: Relevance
“…Cycle time, or generation interval, involves recycling breeding material back into the crossing block as quickly as a breeder can determine that a genotype is above average in breeding value for a desired quantitative trait. Rapid generation advancement, widely known as “speed breeding” ( Watson et al, 2018 ), has been predominantly reported in Fabaceae species for recombinant inbred line production for molecular mapping and QTL discovery ( Lulsdorf and Banniza, 2018 ; Uz Zaman et al, 2019 ; Atieno et al, 2021 ; Dadu et al, 2021 ; Taylor et al, 2021 ). Another practical use of accelerated life cycling is to achieve rapid out-of-season turnover of promising breeding germplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Cycle time, or generation interval, involves recycling breeding material back into the crossing block as quickly as a breeder can determine that a genotype is above average in breeding value for a desired quantitative trait. Rapid generation advancement, widely known as “speed breeding” ( Watson et al, 2018 ), has been predominantly reported in Fabaceae species for recombinant inbred line production for molecular mapping and QTL discovery ( Lulsdorf and Banniza, 2018 ; Uz Zaman et al, 2019 ; Atieno et al, 2021 ; Dadu et al, 2021 ; Taylor et al, 2021 ). Another practical use of accelerated life cycling is to achieve rapid out-of-season turnover of promising breeding germplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Applications of SB include the development of biparental and more complex mapping populations, pyramiding traits, hastening backcrosses, phenotyping adult plant traits, mutant studies, and genetic transformation experiments [ 7 , 29 ]. Recent research has shown the power of combining emerging techniques, such as gene editing, high-throughput phenotyping and genotyping, genomic selection (GS), and MAS, with SB for accelerating crop improvement [ 30 , 40 , 42 , 43 , 44 , 45 , 46 ]. Furthermore, the cost and space requirements for producing a large number of inbred lines can be minimized by planting them at high plant densities [ 47 ].…”
Section: Sb Applications In Research and Breedingmentioning
confidence: 99%
“…Since 2016, SB has been integrated within all cool-season legume public breeding programs in Australia, with more than 45,000 individuals processed through an aSSD platform at the University of Western Australia. The resulting RILs have been used for gene-trait associations [ 43 , 44 , 45 , 46 ], and SB has been integrated with other technologies to accelerate cultivar development pipelines [ 40 ].…”
Section: Model Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…SNP-based markers have contributed enormously to the construction of linkage maps, analysis of genetic diversity, and trait association ( Lombardi et al, 2014 ; Sudheesh et al, 2016a ; Khazaei et al, 2017 , 2018 ; Pavan et al, 2019 ). Recently, genotyping by sequencing (GBS) method and Diversity arrays technology have been used to identify SNPs and develop high-resolution linkage maps ( Ates et al, 2018a ; Pavan et al, 2019 ; Dadu et al, 2021 ).…”
Section: Genomic Innovations Reveal a New Genetic Landscape For Lenti...mentioning
confidence: 99%